Intermolecular acyl-transfer reactions in molecular crystals - Shashidhar, Mysore S.; Krishnaswamy, Shobhana (Accounts of Chemical Research, 2019)
CONSPECTUS: It is far more difficult to recognize and predict the chemical reactions that a molecule of an organic compound can undergo in crystalline (solid) state as compared to the solution state (the "organic functional group" approach), since the published data on solid-state structure reactivity investigations and correlations are scant. The discovery of the first intermolecular acyl-transfer reaction in molecular crystals of racemic 2,4-di-O-benzoyl-myo-inositol-1,3,5-orthoformate (DiBz) during our attempts to develop methods for the synthesis of phosphoinositols, motivated us to find other molecular crystals capable of supporting similar reactions. Small changes to the molecular structure of DiBz yielded analogues with different crystal structures which showed varying degrees of acyl transfer reactivity as compared to the crystals of DiBz. A systematic investigation of the structures, polymorphism, cocrystallization behavior, and the corresponding reactivity of these crystals allowed us to correlate the acyl transfer reactivity with their structures and inherent noncovalent interactions and provided crucial insights into the mechanism of these reactions. Polymorphs or cocrystals of these compounds exhibited dissimilar reactivities due to differences in the molecular conformation and/or arrangements in their crystals. The knowledge of phase transitions between polymorphs enabled us to control and tune the reactivity in the solid state. We could identify three conditions essential for intermolecular acyl transfer: (i) favorable relative geometry of the electrophile (ester C=O) and the nucleophile (OH), (ii) noncovalent interactions (C-H center dot center dot center dot pi) between the reacting molecules which help in maintaining the facility and specificity of the reaction, and (iii) the presence of channels in the lattice which enable propagation of the reaction in the crystal. Based on this supramolecular structure reactivity correlation, we identified other molecular crystals (composed of molecules of widely different molecular structure from that of DiBz) from a survey of the Cambridge Structural Database (CSD) and predicted their acyl transfer reactivity. The increased availability of user-friendly modern X-ray diffractometers and related software has enabled efficient collection, analysis and interpretation of single crystal X-ray diffraction data, essential for such studies. The rapidly expanding CSD facilitates the identification of crystals with similar structures and reactivity patterns. In a wider perspective, facile reactions in molecular crystals fascinate chemists because these reactions usually exhibit unique product selectivity and have the potential to be developed as sustainable green reactions. We are optimistic that similar approaches for the study of other group transfer reactions in molecular crystals would augment and widen the scope of chemical reactions in molecular crystals in particular and the solid state in general. The ability to predict the reactivity of molecules in their crystals could find applications in organic synthesis, material science and industry. Realization of the involvement of inositol derivatives in cellular processes led to the discovery of cellular signal transduction mechanisms. The ability of inositol derivatives to support facile acyl-transfer reactions in the crystalline state might well have opened a new avenue for research in the area of organic solid-state reactions.